Cyanotic Congenital Heart Disease with Hypoxic Spell by Using Evidence Based Practice - Lertwittayakul, Thidaratana; Plubnil, Wipaporn; Raksaken, Boonbenya (College of Asian Scholar Journal, 2024)
Cyanotic congenital heart disease is a cardiovascular disorder that causes deoxygenated blood to flow from the right side of the heart to the left side of the heart (right to left shunt), causing a mixture of deoxygenated blood and arterial blood, resulting in a rapid decrease in oxygen levels. It is common in children with cyanotic congenital heart disease to have less blood flowing to the lungs, causing hypoxic spells, a dangerous condition that can lead to death if not diagnosed and treated promptly. Therefore, the use of evidence-based nursing care to ensure patient safety is important to help nurses provide effective nursing care.